Practical training report: Royal Malaysia Police College of Kuala Lumpur / Nur Syuhada Mohd Hanapiah - Mohd Hanapiah, Nur Syuhada (Universiti Teknologi MARA, Sarawak, 2016)
Royal Malaysia Police College Kuala Lumpur, better known as MPDRMKL was established on January 31, 1999 and officiated by YAB Tun Mohd Hanif B Omar at the opening ceremony of the inaugural academy policing. Generally, the ground-breaking ceremony for the construction of this college was completed on January 7, 1994 and the construction was carried out on January 16 1996 before fully accepted by the Royal Malaysian Police. Generally, the idea of a Royal Malaysia Police College Kuala Lumpur has been initiated by YAB Tun Mohd Hanif B Omar who was then the Chief of Police. He believes that the need to improve police training institutions existing at that time is very important. Therefore, to meet the needs to improve the quality of police training institutions, he has been working on the idea to realize a high policing institution loans, known as the Royal Police College Kuala Lumpur Malaysia. In line with this statement, MPDRMKL has established 10 sub MPDRMKL institutions under the roof, which is 4 institutions for basic training whilst 5 other institutions is on in-service training. Based on the planning and implementation of the police training to do, it has compiled all training activities more systematically where some institutions provided training have been placed under one leadership and administrative commander. This will further facilitate planning, control, common aspects of finance, logistics training and learning. Apart from that, the Royal Malaysia Police College Kuala Lumpur or employee of the civil servants who worked here were 428 people, with 88 people are referring to senior police officers, 272 people are referring to junior officers and members, personal orderly (contract) is a total of 3 people and 65 people are public officials who served in MPDRMKL.